2010
DOI: 10.1111/j.1467-6486.2010.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Ownership as a Form of Corporate Governance

Abstract: Firm ownership is an increasingly influential form of corporate governance. Although firms might be owned by different types of owners, most studies examine owner influence on a particular firm outcome in isolation. This study synthesizes research from multiple disciplines on different types of owners and offers a unifying framework of governance through ownership. Using this framework, we describe the motivations of various types of owners, the tactics owners use to affect firms in which they are invested, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
298
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(312 citation statements)
references
References 196 publications
4
298
0
10
Order By: Relevance
“…This capital, however, has a cost of losing control to the blockholders. This is because such blockholders will be interested in how the resources of the targeted firms are allocated (Connelly, Hoskisson, Tihanyi, & Certo, 2010). From this view point, different studies have found a negative relationship between blockholders and firm performance (see for example, Rosenstein & Rush, 1990;Bogert, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This capital, however, has a cost of losing control to the blockholders. This is because such blockholders will be interested in how the resources of the targeted firms are allocated (Connelly, Hoskisson, Tihanyi, & Certo, 2010). From this view point, different studies have found a negative relationship between blockholders and firm performance (see for example, Rosenstein & Rush, 1990;Bogert, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing literature reveal that block-holding is an important organizational attribute for effective monitoring of management activities (Mustapha & Che-Ahmad, 2013;Reuer, Tong, & Wu, 2012) These literature suggest different types of block-holders, such as institutional (Mustapha & Che-Ahmad, 2013); individual (Eng & Mak, 2003); inside/outside (Jensen & Meckling, 1976); independent/executive (R. C. Anderson, Mansi, & Reeb, 2003); multiple (Connelly, Hoskisson, Tihanyi, & Certo, 2010); second-largest (Chen, Firth, Gao, & Rui, 2006). Each of these types of block-holding has a distinct role to play in good corporate governance (Hope, 2013).…”
Section: Block-holding (Horizontal-agency-costs)mentioning
confidence: 99%
“…One of the policies that might be affected is compensation. In companies with a high ownership concentration, the major shareholders will have a substantial economic incentive to monitor top management's behaviour (Busta et al, in press), whereas in the companies with dispersed ownership, the individual shareholders are unlikely to have sufficient motivation to do the same (Connelly et al 2010;Filatotchev and Wright 2011;Shleifer and Vishny 1986). Close monitoring reduces the agency costs and directs decisions toward increasing firm value (Busta et al, in press;Shleifer and Vishny 1986).…”
Section: Ownership Concentrationmentioning
confidence: 99%
“…A chairperson 1 who owns shares in the company will be motivated to ensure that the board makes and approves decisions that prioritise the interests of shareholders (Connelly et al 2010). In addition, because the chairperson is the leader of the board, he/she will set the agendas for board meetings (Brickley et al 1997), which designate the contents, process and direction of a meeting.…”
Section: Chairperson Ownershipmentioning
confidence: 99%
See 1 more Smart Citation